Organic Farming as a Model of Sustainable Entrepreneurship - Salar Basiri; Mirmohammad Seyednouri; Ali Farzpourmachiani; Seyedehmona Modaresrad; Mercede Ostadsandiani; Saeid Basiri; Mehdi Farzpourmachiani; Snjezana Baroness Rajacic; Fernando Maldonado Lopes (Journal of Biotropical Research and Nature Technology, 2026)
Organic farming is being proposed as one model of sustainable entrepreneurship because it combines environmental benefits, rural livelihoods, and market-based incentives. This review synthesizes the scientific evidence regarding organic agriculture's performance along environmental, economic, and social dimensions and explores how organic systems create both opportunities and constraints for entrepreneurs. I review meta-analytic and review evidence on yields, profitability, ecosystem services, and resilience; discuss practical and structural barriers related to certification, knowledge, scalability, market access, and policy; and outline strategic responses that entrepreneurs and policymakers can use in scaling sustainable agricultural businesses while minimizing trade-offs. The review draws on peer-reviewed meta-analyses and high-quality reviews and concludes with actionable recommendations for entrepreneurs, investors, and policy makers, along with an agenda for future research.